PANDANGAN EKONOMI ISLAM TERHADAP RIBA - Alivia Maharani; Agita Destiani Putri; Nizma Amanda Rizki; Roni Hidayat (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the Islamic economic perspective on riba and its implications in the modern financial system. Riba is strictly prohibited in Islam as it involves elements of injustice and economic exploitation. This research employs a qualitative approach with a normative method through library research. The data used are secondary data obtained from the Qur’an, Hadith, books, and scientific journals related to Islamic economics and riba. The findings indicate that riba has substantial similarities with interest in the modern financial system, particularly due to the predetermined additional payment without risk-sharing. Furthermore, riba has negative impacts on economic and social structures, such as increasing wealth inequality, debt burdens, and the potential for financial crises. As an alternative, Islamic economics offers a profit and loss sharing system that is more just and sustainable. Therefore, the prohibition of riba is not only normative but also relevant in creating a stable and equitable economic system.